2022
DOI: 10.1097/md.0000000000031439
|View full text |Cite
|
Sign up to set email alerts
|

The clinical prognostic value of lncRNA FOXP4-AS1 in cancer patients: A meta-analysis and bioinformatics analysis based on TCGA datasets

Abstract: Background: The mortality and recurrence of patients with cancer is of high prevalence. Long non-coding RNA (lncRNA) forkhead box P4 antisense RNA 1 (FOXP4-AS1) is a promising lncRNA. There is increasing evidence that lncRNA FOXP4-AS1 is abnormally expressed in various tumors and is associated with cancer prognosis. This study was designed to identify the prognostic value of lncRNA FOXP4-AS1 in human malignancies. Methods: We searched electronic databases up to April 29, 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Bioinformatics is an emerging interdisciplinary field that studies a variety of omics data, including transcriptomics, proteomics, and other biological data. The research methods mainly include the collection (collection and screening), processing (editing, sorting, management, and display), utilization (calculation and simulation), and analysis of biological data ( 9 , 10 ). Experience has shown that bioinformatics technology has great application value in the screening of disease biomarkers, which is of great significance for the diagnosis, treatment, and prognosis of diseases, and can provide a more comprehensive and profound understanding of diseases ( 11 - 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Bioinformatics is an emerging interdisciplinary field that studies a variety of omics data, including transcriptomics, proteomics, and other biological data. The research methods mainly include the collection (collection and screening), processing (editing, sorting, management, and display), utilization (calculation and simulation), and analysis of biological data ( 9 , 10 ). Experience has shown that bioinformatics technology has great application value in the screening of disease biomarkers, which is of great significance for the diagnosis, treatment, and prognosis of diseases, and can provide a more comprehensive and profound understanding of diseases ( 11 - 14 ).…”
Section: Introductionmentioning
confidence: 99%